(3JMdjd GdSdGSd GdRefjIs (3JWHjbGJ HGSJNOGe HQeLjI (Bstatas - (3Hf bOhQ(B, (3CThGbs; (3eOjGfj, eMeOs ((3GdLRGFQs (3OGQ GdcJGH GdYQHjs, 2021)
(3eaGgje CSGSjI, echfGJ GdSdGSd GdRefjI, CSGdjH GdeJhSWGJ GdeJMQcI, bjGS GdGJLGg GdYGe, GdJfHD HhLhO GdJCKjQGJ GdehSejI, GdJegjO GdCSj, JMdjd GdGQJHGW hGdGfMOGQ, GSJNOGeGJ hJWHjbGJ HQfGeL (Bstata (3aj JMdjd GdSdGSd GdRefjI(B.s
Keywords: (3GdGMUGAs; (3GdSdGSd GdRefjIs